(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2023)
This study aims to compare and analyze levels of Endothelin-1, Nitric Oxide and roll over test in preeclampsia and normotensive pregnancy. This study was an analytic cross sectional research conducted in Dr. Wahidin Sudirohusodo Hospital, Barabaraya, Mamajang and Antang Health Center in February-June 2020. This study was financed by internal grant UNHAS in 2020 with contract number 1585/UN4.22/PT.01.03/2020. The subjects in this study were women aged 20-35 years with a single pregnancy, above 20 weeks gestational who were divided into 2 grups of 50 preeclampsia and 100 normotensive. ET-1 and NO levels was checked using ELISA Method and ROT was measured by mercury spignomanometer. The research results show that ET-1 and NO levels serum were higher in preeclamptic group (42.27±9.24 vs 37.13±9,44; p=0.002 and 176.43±50.8 vs 152.75±51.3; p=0.012). ROT were higher in preeclamptic group (23.40±8.77 vs 19.70±8.69; p=0.026).